2015
DOI: 10.1097/jom.0000000000000319
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Antigen and Perfluoroalkyl Acids in the C8 Health Study Population

Abstract: Purpose:To inform questions raised by inconsistent findings regarding an association between perfluoroalkyl acids (PFAAs) and prostate cancer by assessing the relationship of PFAAs in human serum to prostate-specific antigen (PSA).Materials and Methods:Using 2005 to 2006 survey data from a large survey population, we compared serum PFAA concentrations in adult males with PSA concentrations adjusted for risk factors including age, body mass index, smoking status, and socioeconomic status.Results:Perfluoroalkyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A case-control general population study by Hardell et al (2014) did find an increase in prostate risk only among subjects with a heredity risk (first-degree relative with prostate cancer) and serum PFOA levels above the median. In a study of community members, Ducatman et al (2015b) did not find an association between prostate-specific antigen (PSA) levels and serum PFOA levels in men 20-49 or 50-69 years of age. In the earliest cancer assessment of workers at the Washington Works facility (Leonard 2006;Leonard et al 2008), an increase in the number of deaths from kidney cancer relative to workers at other regional DuPont facilities was observed; however, the CI included unity.…”
Section: Eriksen Et Al 2009mentioning
confidence: 95%
See 1 more Smart Citation
“…A case-control general population study by Hardell et al (2014) did find an increase in prostate risk only among subjects with a heredity risk (first-degree relative with prostate cancer) and serum PFOA levels above the median. In a study of community members, Ducatman et al (2015b) did not find an association between prostate-specific antigen (PSA) levels and serum PFOA levels in men 20-49 or 50-69 years of age. In the earliest cancer assessment of workers at the Washington Works facility (Leonard 2006;Leonard et al 2008), an increase in the number of deaths from kidney cancer relative to workers at other regional DuPont facilities was observed; however, the CI included unity.…”
Section: Eriksen Et Al 2009mentioning
confidence: 95%
“…No associations between serum PFNA levels and breast cancer(Bonefeld-Jorgensen et al 2014) or prostate cancer(Hardell et al 2014) were found. Serum PSA levels were not associated with serum PFNA levels in men participating in the C8 Health Study(Ducatman et al 2015b).…”
mentioning
confidence: 98%
“…• Concerning results on prostate cancer form the C8 cohort, a cross-sectional study by Ducatman et al (2015) using the blood samples collected in 2005-2006, among 25,412 participants, found no association between measured serum levels of PFOA with Prostate-Specific Antigen above 4.0 (686 cases, 2.7%), which is a marker of prostate disease, including prostate cancer.…”
Section: Uric Acidmentioning
confidence: 99%
“…Without replication in another independent study the results from this study are inconclusive. Concerning results on prostate cancer form the C8 cohort, a cross‐sectional study by Ducatman et al. () using the blood samples collected in 2005–2006, among 25,412 participants, found no association between measured serum levels of PFOA with Prostate‐Specific Antigen above 4.0 (686 cases, 2.7%), which is a marker of prostate disease, including prostate cancer. Alexander and Olsen () examined association between exposure to PFOS retrospectively according to work history records among 1,400 occupationally exposed workers and bladder cancer. The total number of cancer cases was six from questionnaire survey and 5 from death certificates.…”
Section: Assessmentmentioning
confidence: 99%
“…A case-control general population study by Hardell et al (2014) did find an increase in prostate risk only among subjects with a heredity risk (first-degree relative with prostate cancer) and serum PFOA levels above the median. In a study of community members, Ducatman et al (2015b) did not find an association between prostate-specific antigen (PSA) levels and serum PFOA levels in men 20-49 or 50-69 years of age.…”
Section: Health Effectsmentioning
confidence: 95%